A study to assess the magnitude of atypical pneumonia by serum polymerase chain reaction in children aged 3 years to 18 years at Kempegowda Institute of Medical Sciences hospital, Bengaluru, Karnataka, India - S., Ramya H.; Gopi, Anjana; Elango, Vivetha; Kumar, Mansi (International Journal of Contemporary Pediatrics, 2020)
Background: Atypical organisms are a common causative agent of pneumonia in children more than 3 years of age, causing around 10-30% of the cases. Though atypical pathogens are said to cause relatively milder form of pneumonia as compared to other bacterial and viral pathogens, severe manifestations can also occur. Early identification of these pathogens can help in starting treatment with macrolides, which can reduce the length of hospital stay and mortality. Hence in this study the prevalence of atypical organisms was identified by using serum Polymerase chain reaction (PCR). Methods: This was a prospective observational study conducted in children between 3 years to 18 years of age with clinical diagnosis of pneumonia admitted in wards and PICU in KIMS hospital. Authors excluded Immunocompromised children. Detailed history and clinical examination was done. Investigations - complete hemogram, Chest Xray, blood Culture and sensitivity and serum PCR was done for a sample size of 100 children. Results: In this study among the three atypical organisms, Legionella pneumoniae was identified in 2% of the cases by serum PCR. Conclusions: In this study among the three atypical pathogens authors could only identify Legionella pneumoniae. Prevalence of Legionella pneumoniae was 2%. While treating children aged 3 years to 18 years with pneumonia, a high degree of suspicion of atypical pathogens is required, especially in Legionella because of its high mortality rate. In such circumstances adding macrolides along with other antibiotics will be beneficial to the patients outcome and duration of hospital stay.